Role of phytogenic feed additives in modulating NRF‑2/IL‑1β signaling, immune response, and growth performance in cold‑stressed broiler chickens - Fayed, Rabie H.; Ismael, Elshaimaa; Ibrahim, Marwa; El-Sayed, Amr; Bawish, Basma M. (Journal of Advanced Veterinary Research, 2026)
Cold stress is a significant environmental factor negatively affecting broiler performance, immune competence and respiratory health. The aim of this study was to investigate growth promoting, immunomodulatory, antioxidant and anti-inflammatory effects of phytogenic feed additive (PFA) (Herb-ALLTM RESP) on broiler chickens subjected to cold stress in winter season. A total of 480 one-day-old, Ross 308 broiler chicks were assigned to four groups (120 birds each; four replicates of 30 birds): NT group (control): Normal temperature + basal diet without dietary PFA; NT+PFA group: Normal temperature with 1 kg/ton feed dietary PFA (Herb-ALLTM Resp); LT group: Low temperature without dietary PFA; LT+PFA group: Low temperature with 1 kg/ton feed dietary PFA. Cold stress showed compromised broiler growth performance, decrease antibody titer against Newcastle disease virus (NDV), with down regulation of antioxidant NRF-2 gene and upregulation of pro inflammatory cytokines IL1B gene in tracheal and lung tissue. The PFA supplementations markedly improved broiler body weight, feed conversion ratio, European production efficiency factor, immune response against NDV and antioxidant status (↑NRF-2 gene expression), and decrease in inflammatory conditions (↓ IL1B gene expression in both NT and LT conditions, with a decrease in weekly feed intake in LT environment only. These findings highlight the potential of PFA as a natural strategy to improve the broiler productivity and health under cold stress conditions.